2006
DOI: 10.1007/s10238-006-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum pepsinogen with atrophic body gastritis in Costa Rica

Abstract: Individuals with atrophic gastritis (AG), especially atrophic body gastritis (ABG), are at increased risk of developing gastric cancer. Serum concentrations of pepsinogens (PG) have been proposed as markers for ABG. The aim of this study was to determine the risk factors for AG and ABG and the potential of using serum PG concentrations to detect ABG in a dyspeptic population in Costa Rica, which is one of the countries with the highest incidence and mortality rates of gastric cancer in the world. Seven biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
0
23
0
4
Order By: Relevance
“…1) Chen et al [60] and Sierra et al [61] indicated that male gender and smoking were associated with an increased risk of duodenal ulcer in H. pylori-infected patients. Graham [4] speculated that poor nutrition in childhood and low parietal cell function may leave H. pylori-infected patients open to gastric cancer, whereas good nutrition in childhood and high parietal cell function may precede the development of duodenal ulcer.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 99%
“…1) Chen et al [60] and Sierra et al [61] indicated that male gender and smoking were associated with an increased risk of duodenal ulcer in H. pylori-infected patients. Graham [4] speculated that poor nutrition in childhood and low parietal cell function may leave H. pylori-infected patients open to gastric cancer, whereas good nutrition in childhood and high parietal cell function may precede the development of duodenal ulcer.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 99%
“…Various studies in different populations demonstrated different levels of serum PGI, PGII and the PGI:II ratio (Table I) (19)(20)(21)(22)(23)(24). Serum PG concentrations measured in certain areas of Asia appear to be higher than those in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of H pylori associated gastritis is high from an early age [14] . Recently, we found an association between the PGI/PGII ratio and atrophic body gastritis in dyspeptic patients [15] . In the present study, the same population was analyzed for associations of atrophic body and antral gastritis and presence of peptic ulcers with H pylori CagA + infection and pro-inflammatory interleukin-1 (IL-1) gene polymorphisms.…”
Section: Colonization With Helicobacter Pylori (H Pylori)mentioning
confidence: 91%
“…As previously described [15] , between January and July, 2000, 800 consecutive patients referred to the endoscopy service at the Calderón Guardia Hospital in San José for dyspeptic symptoms were interviewed. This hospital is a tertiary hospital that, however, also provides gastroenterology service at primary and secondary levels.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation